Journal Citations in the Doctoral Dissertations of Engineering and Technology Submitted to the General Universities of Karnataka - Dhanamjaya, M.; Talawar, V. G. (Journal of Information and Knowledge, 2010)
The present study is based on the citations cited in Doctoral dissertations of Engineering and Technology awarded by various general universities of Karnataka. This paper comprising 541 journals containing 7467 citations appeared in 137 Doctoral dissertations awarded during 1961-2008. It was observed that more than 67 percent of the theses were awarded by the Bangalore Unicweairy and University of Mysore. It also noted that majority of (85, 62.04%) doctoral dissertations were awarded in between 1996-2008 and more number of Ph.D degree awarded in Civil discipline. Further the characteristics of references cited by the engineers and technologists in their Ph.D theses were studied. The results and discussions with regard to bibliographic form, languages, country, subject, authorship pattern and ranking of journals are presented in different tables and figure with some well known statistical and Bibliometric parameters have been applied for the study.